Penerapan Metode Mind Mapping untuk Meningkatkan Keterampilan Peserta Didik - Iis Nur Khasanah; Nanik Ulfa (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
The research is based on students low average score in Bahasa Indonesia skill on fifth grade student at MI Islamiyah Popoh especially in explaining historical narrative text Theme 7 Subtheme 2 lesson 6. The purpose of this research is to improve students skill by using Mind Mapping method in the indicator of present informations. This method is expected to assist student in learning Bahasa Indonesia. The result of research showed that implementing Mind Mapping can improve students skll in explaining information. First cycle of evaluation showed there were 56% students who didn’t passed the minimum completness criteria, 44% studens passed the minimum criteria. The minimum completeness criteria set is 75 and classically 80% students passed. In the second cycle, there was a significant increase with a percentage of 19% of students who had not completed and 81% of students had completed with a class average of 82.8.